Find the last three digits of the number of 599-tuples ( x 1 , x 2 , … , x 5 9 9 ) of integers where 0 ≤ x i ≤ 5 9 8 , for i = 1 to 599, such that x 1 2 − x 2 2 + x 3 2 − x 4 2 + ⋯ − x 5 9 8 2 + x 5 9 9 2 ≡ 1 ( m o d 5 9 9 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
First note that 599 is prime.
For a odd number n let N n be the number of solutions of x 1 2 − x 2 2 + x 3 2 − x 4 2 + ⋯ + x n 2 ≡ 1 ( m o d 5 9 9 ) , where 0 ≤ x i ≤ 5 9 8 , for i = 1 to n . We need to know the last three digits of N 5 9 9 .
Consider now the odd number n ≥ 3 .
Let t ≡ x 1 − x 2 ( m o d 5 9 9 ) , i.e. x 1 ≡ x 2 + t ( m o d 5 9 9 ) . Replacing in the principal equation we get: t 2 + 2 x 2 t + x 3 2 − x 4 2 + ⋯ + x n 2 ≡ 1 ( m o d 5 9 9 ) .
If t = 0 we get N n − 2 solutions for the ( n − 2 ) -tuple ( x 3 , … , x n ) , thus we get 5 9 9 N n − 2 solutions of the form ( m , m , x 3 , … , x n ) , where m can take any value between 0 and 598.
If t = 0 we get exactly one possible value of x 2 given the values x 3 , … , x n (here we use the fact that 599 is a prime number). Thus, if we select the values of x 3 , … , x n then the value of x 2 is determined and then the value of x 1 is also determined, since x 1 ≡ x 2 + t ( m o d 5 9 9 ) . Therefore, in this case we have 5 9 9 n − 2 solutions for each value of t and the total number of solutions is 5 9 8 ⋅ 5 9 9 n − 2 since t can take 598 values.
Hence we conclude that N n = 5 9 9 N n − 2 + 5 9 8 ⋅ 5 9 9 n − 2 , for any odd number n ≥ 3 .
In the other hand, we know that N 1 = 2 , then N 3 = 5 9 9 × 2 + 5 9 8 × 5 9 9 = 5 9 9 2 + 5 9 9 , and N 5 = 5 9 9 × N 3 + 5 9 8 × 5 9 9 3 = 5 9 9 ( 5 9 9 2 + 5 9 9 ) + ( 5 9 9 − 1 ) × 5 9 9 3 = 5 9 9 4 + 5 9 9 2 , and by an induction we can conclude that N n = 5 9 9 n − 1 + 5 9 9 2 n − 1 , for each odd n .
Therefore, we have N 5 9 9 = 5 9 9 5 9 8 + 5 9 9 2 9 9 .
By the Binomial Theorem: 5 9 9 2 9 9 = ( 6 0 0 − 1 ) 2 9 9 ≡ ( 1 2 9 9 ) 6 0 0 1 ( − 1 ) 2 9 8 + ( 0 2 9 9 ) ( − 1 ) 2 9 9 ( m o d 1 0 0 0 ) , then 5 9 9 2 9 9 ≡ 6 0 0 × 2 9 9 − 1 ≡ 3 9 9 ( m o d 1 0 0 ) . Squaring we get 5 9 9 5 9 8 ≡ 2 0 1 ( m o d 1 0 0 0 ) , therefore N 5 9 9 ≡ 2 0 1 + 3 9 9 ≡ 6 0 0 ( m o d 1 0 0 0 ) .